Written surgical informed consent elements in pediatric differences of sex development: pediatric urologist and endocrinologist perspectives - Lapham, Zoe K.; Gardner, Melissa; Sheinker, Sydney; Suorsa-Johnson, Kristina I.; Kogan, Barry A.; Lee, Peter A.; Sandberg, David E. (Frontiers in Urology, 2023)
Introduction: Elective aspects of surgical management of pediatric differences of sex development (DSD) are associated with controversy. We examined pediatric urologist and endocrinologist perspectives regarding recommended and existing informed consent elements for written consent documents prior to pediatric genital surgery. Methods: Focus groups with pediatric urologist and endocrinologist members of the Societies for Pediatric Urology (SPU, n=8) or Pediatric Endocrine Society (PES, n=8) were held to identify elements of informed consent for DSD-related urogenital surgery. Elements were subsequently included in web-based surveys in 2003 and 2020 (SPU: n=121 and 143; PES: n=287 and 111, respectively). Participants rated their level of agreement with including each element in informed consent documents. In 2020, participants reported whether documents they use in clinical practice incorporate these elements. Results: Focus groups identified four elements of informed consent: on-going debate over pediatric genital surgery; potential needs for multiple procedures; possible gender change and surgical reversal; and non-surgical alternatives. Across both years and both specialties, a majority (79% to 98%) endorsed the four elements, with significant between-group differences. Significantly more PES than SPU participants reported not knowing whether specific elements were included in current written informed consent; of those who knew, the majority (66% to 91%) reported inclusion. Discussion: Specialists agree with including these four elements in written informed consent documents. Endocrinologists are not always familiar with the exact elements included. The degree to which non-surgeon members of the care team should be involved in the written informed consent process is an open question.